DEALCALIZATION OF SOUTHERN CIANJUR BENTONITE USING AMMONIUM HYDROXIDE AND CITRIC ACID - YUHELDA YUHELDA (Indonesian Mining Journal, 2006)
Dealcalization of southern Cianjur bentonite has been done to improve bentonite quality by reducing the alkali element (Na and Ca) content as impurities. The experiment used ammonium hydroxide and citric acid. The reaction parameters such as particle size, solution concentration, percent solid, time and contact temperature were optimized. Results of dealcalization using ammonium hydroxide ob- tained the optimum condition at particle size of -200+325 mesh, concentration of 4 N, percent solid of 10%, contact time of 36 hours and temperature of 100oC with recovery as much as 32.55% for Na and 29.14% for Ca. Meanwhile, dealcalization using citric acid, got optimum condition at particle size of - 325 mesh, concentration of 2N, percent solid of 10%, contact time of 24 hours, temperature of 100oC with recovery as much as 33.01% for Na and 30.07% for Ca. The results also showed that both solutions gave better recovery for Na rather than for Ca. In conclusion, experiment using citric acid was better than using ammonium hydroxide as demonstrated by its higher recovery of alkali elements. However, results of this work have not met the standards of bentonite for catalyst hydrocarbon crac- king.